2016
DOI: 10.1016/bs.enz.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Replication Initiation in Bacteria

Abstract: The initiation of chromosomal DNA replication starts at a replication origin, which in bacteria is a discrete locus that contains DNA sequence motifs recognized by an initiator protein whose role is to assemble the replication fork machinery at this site. In bacteria with a single chromosome, DnaA is the initiator and is highly conserved in all bacteria. As an adenine nucleotide binding protein, DnaA bound to ATP is active in the assembly of a DnaA oligomer onto these sites. Other proteins modulate DnaA oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 167 publications
(199 reference statements)
0
54
0
Order By: Relevance
“…352Earlier, it has been shown that ATP hydrolysis by DnaA is required for melting of AT rich 353 region in oriC followed by initiation of replication(Messer, 2002; Chodavarapu & Kaguni, 354 16 2016). The oligomerisation of both DnaA and DnaB is required for their sequential loading at 355 oriC, unwinding of DNA duplex and generation of replication fork, respectively(Arai and 356 Kornberg, 1981;Chodavarapu & Kaguni, 2016;Patel and Picha, 2000). Here, we report that 357…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…352Earlier, it has been shown that ATP hydrolysis by DnaA is required for melting of AT rich 353 region in oriC followed by initiation of replication(Messer, 2002; Chodavarapu & Kaguni, 354 16 2016). The oligomerisation of both DnaA and DnaB is required for their sequential loading at 355 oriC, unwinding of DNA duplex and generation of replication fork, respectively(Arai and 356 Kornberg, 1981;Chodavarapu & Kaguni, 2016;Patel and Picha, 2000). Here, we report that 357…”
mentioning
confidence: 80%
“…It has been shown in E. coli that DnaA-ATP oligomer binds to DnaA 50 boxes at oriC and unwinds the adjacent AT rich region. Subsequently, a hexameric complex 51 of replicative helicase DnaB and its loader DnaC (DnaB 6 -DnaC 6 ) is recruited to the unwound 52 region in oriC resulting to the formation of pre-priming complex (Skarstad and Katayama,53 2013; Chodavarapu and Kaguni, 2016). This provides the site for binding of primase and 54 activation of various events required for the progression of replication complex comprised of 55 DNA polymerase III holoenzyme.…”
Section: Introduction 42mentioning
confidence: 99%
See 1 more Smart Citation
“…In all bacteria, DNA replication is a tightly regulated process that occurs with high fidelity and efficiency, and is essential for cell survival. The process involves many different proteins that are required for the replication process itself, or to regulate and aid replisome assembly and activity ( Katayama et al, 2010 ; Murray and Koh, 2014 ; Chodavarapu and Kaguni, 2016 ; Jameson and Wilkinson, 2017 ; Schenk et al, 2017 ). Replication initiation and its regulation arguably are candidates for the search for novel therapeutic targets ( Fossum et al, 2008 ; Grimwade and Leonard, 2017 ; van Eijk et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA replication in E. coli initiates at a single origin, oriC , by a mechanism that requires the DnaA protein (Crooke et al ., ; Margulies and Kaguni, ; Kaguni, ; Duderstadt et al ., ; Leonard and Grimwade, ; Chodavarapu and Kaguni, ). The ATP‐bound form of the DnaA replication initiator protein (DnaA‐ATP) is active for initiation of replication.…”
Section: Introductionmentioning
confidence: 99%